PENGEMBANGAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN ADMINISTRASI INFASTRUKTUR JARINGAN DI SMK NEGERI 1 IV KOTO AUR MALINTANG KELAS IX TKJ - Renggy Hermansyah; Faiza Rini; Ami Anggraini Samudra (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This thesis discusses (1) the process of developing Canva-based learning media for the subject of Network Infrastructure Administration at SMK Negeri 1 IV Koto Aur Malintang, and (2) the level of validity and practicality of the media after being tested on teachers and students. The study was motivated by the fact that learning in this subject is still dominated by lecture methods, with limited use of varied media and low student motivation, which has an impact on learning outcomes that remain below the Minimum Mastery Criteria (KKM). Therefore, it is necessary to develop an alternative learning medium that is attractive, interactive, and aligned with technological advancements. The main objective of this research is to produce a Canva-based learning media that can facilitate students in understanding the subject matter and assist teachers in enriching their instructional methods. This study employed a Research and Development (RD) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were the teacher of Network Infrastructure Administration and Class XI TKJ students at SMK Negeri 1 IV Koto Aur Malintang in the 2023/2024 academic year. Data were collected through validation questionnaires completed by media and material experts, as well as practicality questionnaires filled out by teachers and students. The results of the media validation showed a score of 91.67%, categorized as very valid, while the material validation reached 92%, also categorized as very valid. The practicality test indicated that teachers gave a score of 84.38% (very practical), while students gave 78.24% (very practical). These findings confirm that the Canva-based learning media developed is not only valid in terms of content and design but also practical, easy to use, and suitable for both teachers and students. In conclusion, the Canva-based learning media for the subject of Network Infrastructure Administration has proven to be very valid and very practical, and thus feasible to be applied as an alternative learning medium. This media is expected to enhance students’ learning motivation, create a more interactive classroom atmosphere, and provide a meaningful contribution to improving the quality of the teaching and learning process at SMK Negeri 1 IV Koto Aur Malintang.